Additive manufacturing of aluminium oxide with gelatin as rheological modifier - Guo, Yang (Nanyang Technological University, 2022)
Direct ink writing (DIW) is an extrusion-based 3D printing technique. Recently, the advancement using DIW in ceramic has been very challenging due to the compromise between shape retention and flowability and poor scalability. The rheological properties like shape retention and flowability of the ceramic ink are the factors to be optimized and studied in detail. Therefore, this report focuses on the rheological study followed by DIW of Aluminium Oxide (Al2O3) using gelatin as a rheological modifier. By adding small amount of gelatin, we can alter the rheological behaviour of the ink and print patterned structures in three dimensions. Different weight percentages of gelatin and different printing parameters are explored and optimized to achieve the desired 3D structure. The study has potential uses in biomedical and tissue engineering applications.